PENGARUH ALAT PERMAINAN EDUKATIF DASUKA (DADU SUKU KATA) TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI TK MARKUS - Ariell Jevera; Dwi Septi Anjas Wulan (STKIP Subang, 2026)
This study aims to determine the effect of educational game tools (APE) Dasuka (syllable dice) on the early reading ability of children aged 5-6 years in Markus Kindergarten. This study is motivated by the fact that there are still children aged 5-6 years who have difficulty in recognizing letter sounds, reading syllables, and reading simple words. In addition, the lack of use of interesting learning media and in accordance with the characteristics of early childhood needed to support the development of early reading skills. This study uses a quantitative approach with a Pre-Experimental research type and a One Group Pre-test Post-test design. The population in this study was 27 children aged 5-6 years in Markus Kindergarten, with a sample of 9 children selected using a purposive sampling technique. Data were collected through observation and analyzed using descriptive statistics, the Wilcoxon Signed Rank Test, and the N-Gain Test. The results of the study showed that the average child's early reading ability increased from 20.44 in the pre-test to 34.33 in the post-test Wilcoxon Signed Rank Test results. The Rank Test obtained an Asymp, Sig (2-tailed) value of 0.008 < 0.05, so there is a significant difference between children's initial reading ability before and after treatment. The N-Gain test results show an average value of 0.7646 which is included in the high category. Thus, it can be concluded that the APE Dasuka (syllabic dice) has a significant effect on the initial reading ability of children aged 5-6 years at Markus Kindergarten